2019
DOI: 10.1080/09644016.2019.1565679
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for successful environmental justice mobilizations: an analysis of 50 cases

Abstract: The environmental justice (EJ) literature can benefit from comparative analysis that helps to identify conditions for more and less successful outcomes. A data set of 50 EJ cases in the U.S. was developed with high and low remediation as the outcome. Causal conditions were selected on theoretical grounds, and included five mobilizing strategies (local and state government coalitions, federal government attention, civil disobedience, litigation, and national NGO support) and three general conditions (absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
(15 reference statements)
2
16
0
Order By: Relevance
“…Understanding how civil society movements mobilize successfully is important for developing effective support ( Hess and Satcher, 2019 , Zabala, 2019 ). While successes take many forms (e.g.…”
Section: Environmental Defenders and Successful Mobilization Strategimentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding how civil society movements mobilize successfully is important for developing effective support ( Hess and Satcher, 2019 , Zabala, 2019 ). While successes take many forms (e.g.…”
Section: Environmental Defenders and Successful Mobilization Strategimentioning
confidence: 99%
“… Del Bene et al, 2018 , Gerber, 2011 , Haslam and Ary Tanimoune, 2016 , Jeffords and Thompson, 2016 , Martinez-Alier et al, 2016a , Pérez-Rincón et al, 2019 ). Comparative analysis of the conditions leading to success for environmental movements have been rare (see however Aydin et al, 2017 , Bebbington et al, 2008 , Hess and Satcher, 2019 ) and large global analyses have not been done at all.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread failure to attain procedural justice in the siting of power lines and other energy infrastructure can motivate other repertoires of action by affected communities (Cuppen 2017, Hess andSatcher 2019). Often their mobilizations involve forming coalitions across a wide range of different groups, and the frames noted above become attached to different categories of coalition members.…”
Section: Just Outcomesmentioning
confidence: 99%
“…The two categories tend to be inversely related, and institutional tactics tend to be more prominent where there is support from actors in the government (Sherman 2011). Litigation is one of the possible institutional tactics, but it is not always effective, and it is difficult to find general patterns that relate litigation to outcomes (Hess and Satcher 2019).…”
Section: Just Outcomesmentioning
confidence: 99%
“…In a study of opposition to proposed nuclear waste sitings, Sherman (2011) found that a combination of strong community opposition with support from local and state government officials was associated with a successful outcome defined as an end to the siting process. Likewise, in comparative analyses of environmental justice cases, researchers have found that at least some support from government officials has played an important role in successful outcomes for communities (e.g., Grant 2003;Hess and Satcher 2019;McAdam and Boudet 2012). Although this work is focused on the oppositional struggles of local environmental justice cases, it is convergent with the quantitative research that links policy adoption to a strong civil society, public participation, and policy entrepreneurs who may include government officials such as city council members and sustainability officers (e.g., Kalafatis 2018; Portney and Berry 2010).…”
Section: Policy Adoption: Conditions Coalitions and Framesmentioning
confidence: 99%